2020
DOI: 10.3390/nu12020589
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Mother’s Own Milk with Donor Milk in Infants with Gastroschisis or Intestinal Atresia: A Retrospective Study

Abstract: Background: Mother’s own milk (MOM) improves in-hospital outcomes for preterm infants. If unavailable, donor milk (DM) is often substituted. It is unclear if DM vs. formula to supplement MOM is associated with improved in-hospital outcomes in term/late preterm surgical infants with gastroschisis or intestinal atresia. Methods: This retrospective study included infants born ≥33 weeks gestational age (GA) with a birth weight of >1500 g who were admitted to a quaternary neonatal intensive care unit (NICU). Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, the value of exclusive B/LPOM diets and the need for lactation support for surgical infant parents has been increasingly recognized. Existing publications have concluded that exclusive B/LPOM diets are similarly protective for term surgical infants [1][2][3]5,8,46 and that feasible strategies to prevent lactation cessation are needed. 10,14,17,27 As this area of research continues to grow, it is likely that there will be an increased demand for the prioritization of B/LPOM diets and implementation of lactation support interventions for all vulnerable infant populations-not just those born preterm.…”
Section: Critical Need For Early and Continued Lactation Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the value of exclusive B/LPOM diets and the need for lactation support for surgical infant parents has been increasingly recognized. Existing publications have concluded that exclusive B/LPOM diets are similarly protective for term surgical infants [1][2][3]5,8,46 and that feasible strategies to prevent lactation cessation are needed. 10,14,17,27 As this area of research continues to grow, it is likely that there will be an increased demand for the prioritization of B/LPOM diets and implementation of lactation support interventions for all vulnerable infant populations-not just those born preterm.…”
Section: Critical Need For Early and Continued Lactation Supportmentioning
confidence: 99%
“…Increasing the prevalence of exclusive B/LPOM diets among medically vulnerable infants may effectively mitigate both short-and long-term adverse health outcomes associated with birth defects and neonatal surgery, namely feeding intolerance, necrotizing enterocolitis or mesenteric ischemia, and poor growth. [1][2][3]8 Further, providing milk for their critically infant has tremendous benefits for the emotional, physical, and mental well-being of the parent providing milk. 10,14 Therefore, quality, evidencebased lactation support is essential to ensure that copious milk production is established and maintained.…”
Section: Critical Need For Early and Continued Lactation Supportmentioning
confidence: 99%
“…Since then, new avenues of research have established that, when used in the context of optimal lactation support, DHM can be supportive of the establishment of maternal lactation, improved parental wellbeing, maternal psychological health and infant outcomes (5,6,7,8,9). DHM availability may also have positive impacts on infant and maternal health beyond the preterm population (7,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Parent's own milk (parental milk) diets and direct chest/breastfeeding have been shown to mitigate adverse clinical outcomes in medically complex infants and infants with birth defects 3–5,7–12. Mechanisms of protection are related to both the nutritive and bioactive composition of parental milk 10,13. Furthermore, as direct chest/breastfeeding is the physiologic norm for infant feeding, direct chest/breastfed infants with noncraniofacial birth defects have demonstrated more rhythmic feeding patterns, better oxygen levels and energy conservation during feeding, and achieve higher rates of growth than their bottle-fed counterparts 5,14.…”
mentioning
confidence: 99%
“…Birth defects range in incidence, severity, and prognosis based on affected body systems, and neonatal surgery is often necessary for palliation and survival. Abnormal underlying structural or functional physiology and associated treatment modalities predispose these infants to inflammatory disorders, recurrent infections and sepsis, delayed neurodevelopment, malnutrition and feeding intolerance, prolonged hospitalizations, and death 3–13…”
mentioning
confidence: 99%